Developmental biology of gastrointestinal hormones - ESPE Advanced Seminar in Developmental Endocrinology 2016 : Ulm, Germany); Wabitsch, Martin; Posovszky, Carsten 1971- (Basel : Karger, 2017)
The gut not only represents the largest endocrine organ of the human body but is also profoundly involved in the control of metabolism through peptide hormones. Therefore, gastrointestinal hormones are acting via autocrine, paracrine, and classical endocrine pathways and regulate e.g. digestion, hunger, and satiety. Furthermore, they are important regulators of body weight, growth, and glucose metabolism, as well as of mood and behavior. Physicians and scientists in the field of pediatric endocrinology and diabetes, as well as in pediatric gastroenterology, require an extensive understanding of the origin of enteroendocrine cells, factors controlling their differentiation, hormone gene expression, secretion, function and, finally, the complex interaction with other organs, especially the central nervous system. In order to meet these needs, experts in the field have written up-to-date, comprehensive, and illustrated reviews presenting the current knowledge in the field of gastrointestinal endocrinology with a pediatric view. Those reviews comprise this latest volume of Endocrine Development.
A la cabeza del título: 10th ESPE Advanced Seminar in Developmental Endocrinology, Ulm, June 3-4, 2016
Keywords: HORMONAS GASTROINTESTINALES; GASTROENTEROLOGÍA PEDIÁTRICA; ENDOCRINOLOGÍA PEDIÁTRICA